Kekerabatan Bahasa Rejang di Kelurahan Kepala Siring Kecamatan Curup Tengah Kabupaten Rejang Lebong dan Bahasa Minangkabau di Desa Batang Kabung Kecamatan Pariaman Timur Kota Pariaman - Aisyah Nurul Aini; Ermanto (Persona: Kajian Bahasa dan Sastra, 2023)
The objectives in carrying out this research study were (1) to determine how the percentage level of kinship of the languages to be studied in that area; (2) to determine the length of time of separation between the languages studied in the region; and (3) to describe sound correspondences between the languages studied in the region. Furthermore, in this study using quantitative methods and qualitative methods. The objects analyzed in the implementation of this research study were the Rejang language in Kepala Siring Village, Curup Tengah District, Rejang Lebong Regency and the Minangkabau language in Batang Kabung Village, East Pariaman District, Pariaman City. As for the research instrument, there are 200 Morris Swadesh basic vocabulary and 300 cultural vocabulary that have been compiled and adapted to the conditions of the area where the language area is used. This study uses the proficient method which is known to be in collecting research data. Furthermore, the percentage of kinship level of the two languages is calculated using the lexicostatistical method which is 38.5%. Meanwhile, the length of time the separation was for 2200 years ago or around 177 BC. As for the total cognates of these two languages, based on 500 vocabularies, there are 210 vocabularies. As well as found five forms of sound correspondence between languages, namely 40 forms of similar vocabulary, 59 sound substitutions or more commonly known as phonemes, 38 sound reduction vocabulary or more commonly understood as phonemes, 72 additional sound/phoneme vocabulary, and 1 metathesis vocabulary.